An episiotomy scar site endometriosis: a rare case report and review of literature - Thirupathi, Kalaivani; Rengaraj, Nithya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Endometriosis can be defined as the presence and growth of functioning endometrial tissue (glands and or stroma) outside the endometrium. Occasionally, surgical scars are the sites of endometriotic implantation particularly perineal scars (episiotomy). Perineal scar endometriosis is a very rare condition, its incidence rate was about 0.03-0.15%. Perineal scar endometriosis mainly affects young females at the episiotomy site following a previous vaginal delivery. A 29 years old patient presented with swelling at the site of episiotomy which was associated with pain during menstruation. On examination a palpable mass was revealed without induration at close proximity to episiotomy scar site during menstruation. MRI pelvis is the most commonly used imaging technique for the diagnosis of perineal endometriosis as well as to assess the deeper extent of the lesion. Mass excised and sent for histopathological examination. Wide local excision is the definitive treatment for surgical site endometriosis. Follow up is recommended for recurrence. The rare possibility of malignant transformation, can be excluded by histopathological examination of excised tissue.